ANALISIS KEPUASAN MASYARAKAT DALAM PENGURUSAN SURAT IJIN USAHA PERDAGANGAN AGRIBISNIS MELALUI BADAN PELAYANAN PERIJINAN TERPADU SATU PINTU DAN PENANAMAN MODAL KOTA DENPASAR - FEBRYANA, NI PUTU VIVI; Susrusa, Ketut Budi; Sudarma, I Made (JURNAL MANAJEMEN AGRIBISNIS; Vol 5 No 2 (2017): OKTOBER 2017DO - 10.24843/JMA.2017.v05.i02.p04, 2017)
The main function of the government is to serve the community. Increasing public satisfaction is one of the efforts to improve the quality of public services. Trading business license services for agricultural investment activities (agribusiness) is one of the licensing services provided by One Stop Service Permit and Investment Board (BPPTSP and PM) in Denpasar City. This study aims to analyze the Public Satisfaction in the management of Agribusiness license in BPPTSP and PM of Denpasar City. Analysis method in this study using Partial Least Square (PLS) with the help of Smart PLS Version 3 program that measures the satisfaction of the community in managing the agribusiness license based on three variables namely; service standards, bureaucratic performance, and service quality. The results of this study indicate that the three variables are very positive effect on the satisfaction of the community in managing the business license Agribusiness in BPPTSP and PM Denpasar. Improvement of service standards, bureaucratic performance and service quality in the management of trading business license in BPPTSP and PM of Denpasar City will increase the satisfaction of the public in the business license arrangement, thus the community is increasingly interested to manage the legality of their business independently. Increasing the management of trading business permit, especially in the field of Agribusiness will reduce the number of illegal companies in Denpasar City, so that Agribusiness companies in Denpasar City can operate in the market legally and safely, and people can buy agribusiness’s products safely without fear of harmful content on the product.